(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
The purpose of this study was to investigate the use of Information Communication Technology (ICT) in teaching and Learning in Rachuonyo South District secondary schools. The focus was on three main subject matters: on ICT use and competence, on teacher and student and on ICT infrastructure and teaching practices. The objective of this study was to examine availability of ICT tools for use in enhancing teaching and learning.A descriptive survey design was used. Data from the field was collected through the use of questionnaire and an observation schedule. From the sample area of study, there were 320 students drawn from form four. In addition, 24 teachers, and 8 principals were purposively selected to fill questionnaires designed for them. Reliability of the instruments was addressed through piloting in 5 schools and reliability coefficients were obtained by subjecting the instruments to a Split-half Technique and Spearman â€œBrown Prophesy formulaâ€ .To ensure face and content validity of the research instruments, 2 experts in the department of curriculum studies, faculty of education were requested to scrutinize the research instruments so as to validate them. Data was analyzed using both qualitative and quantitative methods. Qualitative data was analyzed using likert scale and other qualitative data were analyzed in an ongoing process as themes and sub-themes emerged.The findings further indicated that ICT integration realized some challenges such as availability of sufficient number of ICT tools, lack of motivation and support and lack of technical support. The challenges are either teacher-level (Micro-level), school level (Meso-level) or system level (Macro-level). These barriers have hindered successful implementation of ICT into teaching and learning processes. The study also recommended that teachers should be given sufficient training on how to use ICT tools to enhance teaching and learning in schools. The study also recommended that students should be equipped with ICT skills such as Microsoft software applications such as word, excel and access. Finally, further research on the perception of teachers and students towards the use of ICT in enhancing teaching and learning and relevant strategies for using ICT to improve teaching and learning practices should be conducted.